2018
DOI: 10.1038/pr.2017.312
|View full text |Cite
|
Sign up to set email alerts
|

Total brain, cortical, and white matter volumes in children previously treated with glucocorticoids

Abstract: BackgroundPerinatal exposure to glucocorticoids and elevated endogenous glucocorticoid levels during childhood can have detrimental effects on the developing brain. Here, we examined the impact of glucocorticoid treatment during childhood on brain volumes.MethodsA total of 30 children and adolescents with rheumatic or nephrotic disease previously treated with glucocorticoids and 30 controls matched on age, sex, and parent education underwent magnetic resonance imaging (MRI) of the brain. Total cortical gray an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 41 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…We included these two different extra-cerebral pediatric diseases with the aim to control for potential disease-related effects. In previous work, we observed that these patients had lower verbal intellectual abilities (Holm et al, 2015) and smaller total brain volumes as compared to healthy controls (Holm et al, 2018). Furthermore, the children treated with glucocorticoid showed sex-dependent differences in endogenous cortisol profiles compared to healthy controls, with girls having higher cortisol awakening response (CAR) and boys having higher cortisol levels during the day (Vestergaard et al, 2017).…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…We included these two different extra-cerebral pediatric diseases with the aim to control for potential disease-related effects. In previous work, we observed that these patients had lower verbal intellectual abilities (Holm et al, 2015) and smaller total brain volumes as compared to healthy controls (Holm et al, 2018). Furthermore, the children treated with glucocorticoid showed sex-dependent differences in endogenous cortisol profiles compared to healthy controls, with girls having higher cortisol awakening response (CAR) and boys having higher cortisol levels during the day (Vestergaard et al, 2017).…”
Section: Introductionmentioning
confidence: 80%
“…The participants in the present study are the same as in our recent study investigating the effects on glucocorticoid treatment on global structural brain measures (Holm et al, 2018). Therefore, if identical, information on participants, clinical characteristics and background variables is presented between quotation marks followed by the reference to the previous article.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations